# Partial Differential Equations Question: Find an explicit expression for the solution of the IVP [closed]

Find an explicit expression for the solution of the IVP

$$\begin{cases} u_{t}(x,t)+u_{x}(x,t)+u(x,t)=e^{t+2x}\\ \\ u(0,x)=0, \end{cases}$$

by using the method of characteristics

## closed as off-topic by max_zorn, Riccardo.Alestra, mrtaurho, metamorphy, José Carlos SantosJan 21 at 12:12

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "This question is missing context or other details: Please provide additional context, which ideally explains why the question is relevant to you and our community. Some forms of context include: background and motivation, relevant definitions, source, possible strategies, your current progress, why the question is interesting or important, etc." – max_zorn, Riccardo.Alestra, mrtaurho, metamorphy, José Carlos Santos
If this question can be reworded to fit the rules in the help center, please edit the question.

• Hi and welcome to the Math.SE. Questions sounding like "do this for me, please" are poorly received from other members. I you need help, help other users help you for example by explaining what you tried and where did you get stuck. – Daniele Tampieri Jan 20 at 17:08

This is a linear PDE so

$$u = u^h + u^p$$

with

$$u_t^h+u_x^h=-u^h\\ u_t^p+u_x^p+u^p=e^{t+2x}$$

Using the Characteristics method with $$u^h$$ we have

$$\begin{cases} \frac{dt}{d\tau} = 1 & t(0) = 0 & t(\tau) = \tau\\ \frac{dx}{d\tau} = 1 & x(0) = s & x(\tau) = s+\tau\\ \frac{du^h}{d\tau} = -u^h & u^h(0) = \phi(s) & -\ln u^h(\tau) = \phi(s)+\tau \end{cases}$$

or

$$u^h(t,x) = e^{-t}\psi(x-t)$$

regarding the particular we have that $$u^p(t,x) = \frac 14e^{t+2x}$$ verifies the particular equation then

$$u(t,x) = e^{-t}\psi(x-t)+\frac 14e^{t+2x}$$

and for $$t=0$$ we have

$$\psi(x) + \frac 14e^{2x}=0$$

then $$\psi(x) = -\frac 14 e^{2x}$$ and finally

$$u(t,x) = \frac 14\left(-e^{-t}e^{2(x-t)}+e^{t+2x}\right)$$

Yes, by using the method of characteristics, one can find the explicit expression for the solution : $$u(t,x)=\frac14\left(e^{t+2x}-e^{-3t+2x} \right)$$ The question is concise. The answer as well.